2017
DOI: 10.1097/mpg.0000000000001437
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Tissue Transglutaminase Antibodies in Children With Eosinophilic Esophagitis

Abstract: Serum TTG Ab was elevated in almost one-quarter of our total EoE cohort, and at least 20% of these patients did not have potential CD, suggesting EoE is a heterogeneous disease with differing immune mechanisms activated in some patients. These findings also support routine esophageal biopsy during upper endoscopy in children with elevated TTG Ab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Le Fevre et al 29 reported that tTG antibody was elevated in 23% of their EoE cohort, but elevated tTG antibody titres are not specific to CD. Although their study show any correlation between EoE and CD, they also recommended routine oesophageal and duodenal biopsies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Le Fevre et al 29 reported that tTG antibody was elevated in 23% of their EoE cohort, but elevated tTG antibody titres are not specific to CD. Although their study show any correlation between EoE and CD, they also recommended routine oesophageal and duodenal biopsies.…”
Section: Discussionmentioning
confidence: 95%
“…Although an association between CD and EoE has been reported in some studies, 8‐14 some researchers denied this relation 18‐20,29 . Hommeida et al 18 retrospectively reviewed 10.201 children who underwent endoscopic evaluation and found that the prevalence of EoE in children with CD was 1.83% when compared with 5.83% in all children who had EoE and stated that there was no increased risk of EoE in children with CD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated and hypothesized potential causes of elevated tTG‐IgA in pediatric patients without CD, including increased polyclonal IgA production in children with juvenile idiopathic arthritis, an acute immunologic phenomenon in response to infectious disease, and in response to fibrogenesis and apoptosis in patients with end‐stage heart failure (25–28). Additionally, recent studies have reported elevated serum tTG‐IgA in non‐CD patients with EoE (29). The findings of this study support the aforementioned literature.…”
Section: Discussionmentioning
confidence: 99%
“…How specific are elevations in TTG and DGP autoantibodies to celiac disease? Recently, Le Fevre et al have published findings on elevated TTG antibodies in almost a quarter of children with eosinophilic esophagitis ( Le Fevre et al, 2017 ). In addition, they review previous studies in which elevated serum TTG antibodies have been found in non-celiac disease states, including malnourished patients with cerebral palsy, alcohol consumers, and IBD and other autoimmune conditions.…”
mentioning
confidence: 99%